LINGUOCULTURAL FEATURES OF PHRASEOLOGY IN UZBEK AND GERMAN LANGUAGES - Muminova Oftobkhon Karimovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article briefly discusses phraseology in Uzbek and German. The views of the German linguist II Chernishyova on phraseology are theoretically illuminated.